Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3386/w19882
|View full text |Cite
|
Sign up to set email alerts
|

Default and Repayment Among Baccalaureate Degree Earners

Abstract: More than low default rates, lenders are interested in the expected return on their loans. In this paper, we consider a number of other measures of repayment and nonpayment that are likely to be of direct interest to lenders. Using data from the Baccalaureate and Beyond Longitudinal Study, we document repayment and nonpayment outcomes 10 years after graduation for American students receiving BA/BS degrees in 1993. We estimate differences in these outcomes across individual/family background characteristics, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Hillman (2014) employed a logistic regression model to contrast the characteristics of borrowers in student loan repayment who defaulted on their student loans against those who did not and found that African American and Hispanic borrowers were roughly 9% more likely to have defaulted on their debts than non-minority borrowers. This finding is consistent with other studies which suggest that students of color are at greater risk of loan default (Addo et al, 2016; Barone et al, 2005; Christman, 2000; Dynarski, 1994; Flint, 1997; Harrast, 2004; Herr & Burt, 2005; Hillman, 2014; Knapp & Seaks, 1992; Lochner & Monge-Naranjo, 2014; Podgursky et al, 2002; Steiner & Barone, 2014; Volkwein et al, 1998; Woo, 2002b). Notably, recent work by Scott-Clayton, (2018) revealed that Black bachelor’s degree graduates were five times more likely to default than White graduates.…”
Section: Literature Review and Theoretical Perspectivessupporting
confidence: 90%
See 3 more Smart Citations
“…Hillman (2014) employed a logistic regression model to contrast the characteristics of borrowers in student loan repayment who defaulted on their student loans against those who did not and found that African American and Hispanic borrowers were roughly 9% more likely to have defaulted on their debts than non-minority borrowers. This finding is consistent with other studies which suggest that students of color are at greater risk of loan default (Addo et al, 2016; Barone et al, 2005; Christman, 2000; Dynarski, 1994; Flint, 1997; Harrast, 2004; Herr & Burt, 2005; Hillman, 2014; Knapp & Seaks, 1992; Lochner & Monge-Naranjo, 2014; Podgursky et al, 2002; Steiner & Barone, 2014; Volkwein et al, 1998; Woo, 2002b). Notably, recent work by Scott-Clayton, (2018) revealed that Black bachelor’s degree graduates were five times more likely to default than White graduates.…”
Section: Literature Review and Theoretical Perspectivessupporting
confidence: 90%
“…Gender has also been shown to impact default risk; numerous analyses find significantly higher rates of default among male borrowers (Barone et al, 2005; Herr & Burt, 2005; Podgursky et al, 2002; Steiner & Barone, 2014; Woo, 2002b). There are a few studies, however, that find no significant difference between the default rates of male and female borrowers (Christman, 2000; Lochner & Monge-Naranjo, 2014; Volkwein & Szelest, 1995).…”
Section: Literature Review and Theoretical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…If such a pattern holds for more recent cohorts, the true default rates for recent years are probably even higher than the measured ones because some default might be temporarily masked as deferment or forbearance. The default projections for recent cohorts might need to be downgraded even further, since the results of Lochner and Monge-Naranjo (2014) …”
mentioning
confidence: 99%